The Desubstantialization of Subject in Philosophy of M. Heidegger - Gutauskas, Mintautas (Problemos, 2001)
In this article the author discusses Heidegger’s views on the status of subject in his ontology. In the negative conclusions of Kant and Husserl stating impossibility to conceive subject as certain substance Heidegger finds positive possibilities. He desubstantializes the subject describing it’s being as “understanding” and “anxiety”. Rejecting the image of subject as substance, Heidegger describes Dasein as temporal being-in-the world, i.e. as throwness and project. He conceives time as historicity and the space as the situation, both being the modus of existing Dasein.